IMPROVING THE TECHNOLOGY OF PRODUCTION OF NEW TYPES OF RAILWAY WHEELS OPEN JOINT STOCK COMPANY «NIZHNODNІPROVSKY TUBE ROLLING PLANT » - Yarovoi, V. O. (Science and Transport Progress, 2006)
In this paper the grounds of the forging procedure modification while mastering the new type of the railway wheels BA 318 for DB AG certification are reported. The technically based rolling procedure of the wheels rolling with application of the ring-items rolling mill is in the scope of great interest as well. The data of the mastering of the double-flanged crane wheels on the tyre-manufacturing line are cited.